2005
DOI: 10.1149/1.1869232
|View full text |Cite
|
Sign up to set email alerts
|

High Energy-Density Capacitor Based on Ammonium Salt Type Ionic Liquids and Their Mixing Effect by Propylene Carbonate

Abstract: Novel ionic liquids comprised of a quaternary ammonium salt type cation have been applied to an electrolyte for high performance electric double-layer capacitors (EDLCs). The novel ionic liquids (IL-B; N, N-diethyl-N-methyl(2-methoxyethyl) ammonium tetrafluoroborate (DEME-BF 4 ) and IL-T; N, N-diethyl-N-methyl(2-methoxyethyl) ammonium bis(trifluoromethylsulfonyl)imide (DEME-TFSI)) are promising candidates for EDLC electrolytes in terms of a high decomposition voltage (wide voltage window) non-flammability, eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 25 publications
3
52
0
Order By: Relevance
“…This issue is solved here by using a room temperature ionic liquid (RTIL) (17) 1-butyl,3-methylimidazolium chloride ([bmIm][Cl]) (17), which dissolves up to 25% (wt/wt) of unmodified cellulose by using microwave irradiation (18). Interestingly, the ionic nature of RTIL (19) permits it be used as an electrolyte in supercapacitors (20), allowing the assembly of all three components (Fig. 1) (Fig.…”
mentioning
confidence: 99%
“…This issue is solved here by using a room temperature ionic liquid (RTIL) (17) 1-butyl,3-methylimidazolium chloride ([bmIm][Cl]) (17), which dissolves up to 25% (wt/wt) of unmodified cellulose by using microwave irradiation (18). Interestingly, the ionic nature of RTIL (19) permits it be used as an electrolyte in supercapacitors (20), allowing the assembly of all three components (Fig. 1) (Fig.…”
mentioning
confidence: 99%
“…However, we have previously observed that the EDLC using 1M DEME-BF 4 , which a molecular weight of 233.05, has an approximately 10% higher capacitance than a cell using a 1M solution of a conventional ammonium salt, tetraethylammonium tetrafluoroborate (TEA-BF 4 ), which has a molecular weight of 217.6 (Kim et al 2005). However, in the results shown in Fig.…”
Section: Comparison Of Edlc Capacitance and Internal Resistancementioning
confidence: 88%
“…Such electrolytes could find applications in niche markets working at high temperatures or working at low power density but at high voltage (if purity is high). Ionic liquids have been tested as salts in organic electrolyte [266], as presented in Figure 10.25 [267]. Two very interesting studies have been dedicated to these mixtures and have demonstrated encouraging results in order to increase the conductivity of ACN-based electrolytes [268] and ACN-free electrolytes [269].…”
Section: Ionic Liquid Electrolytementioning
confidence: 99%